KOMUNIKASI PEMASARAN SEBAGAI FAKTOR PEMBENTUK CITRA MEREK: STUDI KASUS PADA PT. BPR MITRA KANAKA SANTOSA BANDUNG - Permana, Prama; Nugraha, Galih (Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the effect of marketing communication on brand image at PT. BPR Mitra Kanaka Santosa Bandung, focusing on three dimensions: public relations, advertising, and personal selling. The research is motivated by the increase in promotional activities that have not yet resulted in significant improvements in brand image or customer growth. A quantitative method with a survey approach was employed. The sample consisted of 73 active savings customers selected using probability sampling from a total population of 350 customers. Data were collected using a closed ended questionnaire with a Likert scale, and analyzed using path analysis. The results show that, partially, only personal selling has a significant influence on brand image. Public relations and advertising do not have a significant effect. Simultaneously, the three marketing communication variables do not significantly affect brand image. These findings indicate that direct, personal marketing strategies are more effective in building brand image than one-way communication approaches such as advertising or public relations.